2019
DOI: 10.1155/2019/6340565
|View full text |Cite
|
Sign up to set email alerts
|

Brunner’s Gland Hyperplasias and Hamartomas in Association with Helicobacter pylori

Abstract: Background. The proliferative lesions of the Brunner’s glands (BGs) are hyperplasia and hamartomas, and they are usually asymptomatic and very rarely diagnosed. The aetiology of these lesions is not yet clear. The aim of this study is to evaluate the clinical presentations of patients with BG hyperplasia and hamartomas and to assess the pathological features of these lesions in association with Helicobacter pylori (H. pylori). Methods. Our retrospective study included patients who underwent upper gastrointesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
(81 reference statements)
1
16
0
Order By: Relevance
“…Proliferative lesions of the BGs are uncommon small intestinal lesions, encountered primarily in the proximal duodenum and account for approximately 5–10% of all duodenal masses and less than 1% of all gastrointestinal tumors [ 4 ]. These lesions include hyperplasia/adenoma (nodule/polyp), hamartoma (BGH) and extremely rarely adenocarcinoma [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proliferative lesions of the BGs are uncommon small intestinal lesions, encountered primarily in the proximal duodenum and account for approximately 5–10% of all duodenal masses and less than 1% of all gastrointestinal tumors [ 4 ]. These lesions include hyperplasia/adenoma (nodule/polyp), hamartoma (BGH) and extremely rarely adenocarcinoma [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathogenesis of BG hyperplastic and hamartomatous lesions are not fully understood. The suggested causes are those associated with chronic local irritation, hyperchlorhydria, H. pylori infection, and pancreatic exocrine insufficiency [ 4 ]. Brunner’s gland proliferative lesions can present at any age, but commonly observed between the ages of 50 and 60 years and affect both sexes equally [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another hypothesis is that Hp infection may contribute to the pathogenesis of Brunner's gland hamartoma. Three studies found that patients with Brunner's gland hyperplasia or hamartoma have a high positive Hp infection rate of 56.6-71.0% [21][22][23], but another study reported that none had Hp infection [10] (Table 1). Thus, it is necessary to further analyze the relationship of Hp infection with Brunner's gland hamartoma.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…Another study focused on pathology and also showed the role of H pylori on Brunner's gland hyperplasia and hamartomas in the duodenum 17 …”
Section: Invasive Testsmentioning
confidence: 99%